To perform or not to perform? How strategic orientations influence the performance of Social Entrepreneurship Organizations - Florian Lückenbach; Carsten Baumgarth; Holger J. Schmidt; Jörg Henseler (Cogent Business & Management, 2019)
Social Entrepreneurship Organizations (SEOs) aim to solve social, environmental or societal problems even as they strive to work profitably. The achievement of the social mission also requires economic viability and differentiation from the competition. Acting in contested markets, SEOs must, therefore, adopt a competitive strategy to deliver services and products. While literature concerning achieving competitive advantages through a strategic concept has a long tradition in business management, little is known about how SEOs can use different strategic orientations (SO) to achieve superior performance. Based on a global sample of social entrepreneurs (n = 130), this study assessed the impact of market orientation (MO), entrepreneurial orientation (EO), and brand orientation (BO) on SEO performance. The findings indicate that MO and EO help SEOs to foster social and market performance. Using partial least squares (PLS) path modelling, in conjunction with fuzzy set Qualitative Comparative Analysis (fsQCA), this study also provides new insights into the interplay of SO, illustrating that MO and BO are complementary approaches that contribute to economic performance.
Keywords: 650; Social Entrepreneurship Organization; brand orientation; entrepreneurial orientation; market orientation; performance measurement; partial least squares modelling; fuzzy set qualitative comparative analysis